IMPLEMENTASI ETIKA BISNIS ISLAM DALAM INDUSTRI F&B: STUDI KASUS CAFE LAFAYETTE MALANG - Tanti Alvi Nur ilmi (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2025)
ABSTRAK The food and beverage (F&B) industry is one of the most dynamic and competitive economic sectors, with rapid growth driven by consumer trends that increasingly prioritize quality, innovation, and dining experiences, as well as increasing awareness of sustainability and social responsibility. This study aims to explore the implementation of Islamic business ethics in the F&B industry through a case study at Café Lafayette Malang. The qualitative research methods used include literature analysis, participant observation, and in-depth case studies. The literature analysis provides a theoretical basis for the principles of maqāṣid al sharī’ah, al ṣidq (honesty), ‘adl (justice), and ta’āwun (mutual assistance) in a business context. Field observations include the selection process of halal and environmentally friendly raw materials, café operational practices, modest dress code, Islamic decoration, murottal screenings, and employee-customer management interactions. The case study allows for a contextual understanding of employee welfare policies, Islamic CSR programs, and challenges related to costs and market competition. The results of the study show that Café Lafayette has successfully implemented Islamic business ethics comprehensively from the selection of raw materials and transparency of halal certification to enforcing the etiquette of wearing closed clothing, strengthening the spiritual atmosphere through murottal and Islamic motivation, and social environmental contributions. The implementation of these sharia principles not only increases customer trust and loyalty, but also reduces employee turnover, strengthens a positive reputation in the community, and supports business sustainability. This study recommends optimizing the efficiency of the sharia supply chain, digitizing Islamic ethics services and education, and collaborating with the da'wah community to expand the positive impact and ensure the sustainability of Islamic business practices in the F&B sector.